2002
DOI: 10.2466/pr0.2002.90.3c.1161
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Directed toward Chronic Illness is Resistant to Change Through Education and Exposure

Abstract: In the mid-1980s, research reported that people living with HIV were viewed differently on measures of competence, dependence, morbidity, depression, and moral worth from those living with other chronic illnesses. 443 students were surveyed to evaluate present attitudes in comparison to this earlier research. The usefulness of imaginal exposure, i.e., imagining a loved one living with HIV, in reducing stigma toward people with HIV was also investigated. Analysis indicated no difference in the rating of AIDS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Less than half of the respondents were sympathetic to persons living with HIV who were either homosexual men or women sex workers, while the majority of persons reported sympathetic feelings toward persons living with HIV who were either heterosexual men and women who were not sex workers. This finding supports previous research that has established an association between sexual prejudice and negative attitudes toward persons living with HIV (Breault and Polifroni 1992, Davis et al 1999, Batson et al 2002, Hayes et al 2002, Peltzer et al 2004. Specifically, research has found that persons living with HIV who are perceived to be men who have sex with men or sex workers receive even less sympathy and compassion than those who are not considered to be members of these groups (de Bruyn 1998, ICRW 2002.…”
Section: Discussionsupporting
confidence: 93%
“…Less than half of the respondents were sympathetic to persons living with HIV who were either homosexual men or women sex workers, while the majority of persons reported sympathetic feelings toward persons living with HIV who were either heterosexual men and women who were not sex workers. This finding supports previous research that has established an association between sexual prejudice and negative attitudes toward persons living with HIV (Breault and Polifroni 1992, Davis et al 1999, Batson et al 2002, Hayes et al 2002, Peltzer et al 2004. Specifically, research has found that persons living with HIV who are perceived to be men who have sex with men or sex workers receive even less sympathy and compassion than those who are not considered to be members of these groups (de Bruyn 1998, ICRW 2002.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of stigma on the HIV/AIDS identity incorporation process are well documented (Gurevich, 1996;Lewis, 1994;Sandstrom, 1990). Although AIDS seems to be more stigmatized than HIV, even among those living with HIV or AIDS (Scott, 2009), and studies report a decrease in the stigma of HIV/AIDS (Hayes, Vaughan, Medeiros, & Dubuque, 2002), it is still a reality for people who are HIV positive and it still prevents disclosure, thereby inhibiting the incorporation of HIV/AIDS into one's identity. A recommended strategy for decreasing this stigma is for people to become acquainted with someone who is HIV positive, which can help them become less judgmental and more accepting of PLWHAs (Hayes et al, 2002).…”
Section: Disclosurementioning
confidence: 99%
“…Antistigma interventions remain a low priority for HIV/AIDS programs, mainly because of the difficulty in identifying effective interventions [7]. Population-level research on the structural drivers of HIV stigma will be necessary to inform how and where community-level interventions can be most effective [3,5,19]. …”
Section: Introductionmentioning
confidence: 99%